2014
DOI: 10.1200/jco.2014.32.31_suppl.189
|View full text |Cite
|
Sign up to set email alerts
|

A combined treatment approach for cachexia and cancer-related anemia in advanced cancer patients: A randomized placebo-controlled trial.

Abstract: 189 Background: Cancer progression is characterized by specific energy metabolism alterations and by symptoms including fatigue, anorexia, nausea, depression, which results in cachexia syndrome and compromised quality of life (QL). This condition is often associated to anemia (cancer-related anemia, CRA), which negatively impacts patient QL and disease outcome. Methods: Adult advanced cancer patients with cachexia (i.e., weight loss > 5% in the previous 6 months) and CRA were randomly assigned (1:1 by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Thus, in the tolerance phase, targeting the symptoms consequent to chronic inflammation, such as thrombosis, anemia, anorexia, weight loss, muscle wasting is fundamental for an effective treatment strategy. Therefore, treatment with immunomodulatory and immunosuppressive drugs, such as glucocorticoids and low molecular weight heparin, to prevent or treat the associated thrombotic events, as well as administration of supportive drugs, such as antioxidants and lactoferrin, which help to restore the defective function of the adaptive specific immunity and modulate the altered iron metabolism, as observed in patients with advanced ovarian cancer [ 29 , 139 ], may prove beneficial even in the absence of specific antiviral treatments. In a randomized clinical trial [ 140 ] we have demonstrated in patients with advanced cancer, primarily ovarian cancer, with chemotherapy-related anemia, that lactoferrin mobilized iron storage thereby reducing ferritin levels and increasing iron availability for erythropoiesis and heme proteins synthesis, such as myoglobin and cytochrome chain.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the tolerance phase, targeting the symptoms consequent to chronic inflammation, such as thrombosis, anemia, anorexia, weight loss, muscle wasting is fundamental for an effective treatment strategy. Therefore, treatment with immunomodulatory and immunosuppressive drugs, such as glucocorticoids and low molecular weight heparin, to prevent or treat the associated thrombotic events, as well as administration of supportive drugs, such as antioxidants and lactoferrin, which help to restore the defective function of the adaptive specific immunity and modulate the altered iron metabolism, as observed in patients with advanced ovarian cancer [ 29 , 139 ], may prove beneficial even in the absence of specific antiviral treatments. In a randomized clinical trial [ 140 ] we have demonstrated in patients with advanced cancer, primarily ovarian cancer, with chemotherapy-related anemia, that lactoferrin mobilized iron storage thereby reducing ferritin levels and increasing iron availability for erythropoiesis and heme proteins synthesis, such as myoglobin and cytochrome chain.…”
Section: Introductionmentioning
confidence: 99%
“…Of the full text peer-reviewed manuscripts, the majority reported on randomized controlled trials (RCTs) (n = 18) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], followed by quasi-experimental trials (n = 15) [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66], retrospective cohort observational studies (n = 2) [67,68], and case studies (n = 3) [69][70][71]. Conference abstracts reported on RCTs (n = 3) [72][73][74], quasi-experimental trials (n = 4) [75][76][77][78], and a case study (n = 1) [79]. The two clinical trial registrations consisted of one RCT [80], which was terminated as sample size could not be reached, and one quasi-experimental trial ...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Minerals included were calcium (n = 2) [62,64], iron (n = 2) [68,79], and selenium (n = 1) [75]. Antioxidants (other than vitamins and minerals) included carbocysteine (n = 4) [42,44,54,74], lipoic acid (n = 4) [42,44,54,74], quercetin (n = 2) [44,54], curcumin (n = 2) [73,77], and lycopene (n = 1) [66].…”
Section: Vitamins Minerals and Other Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…95 A combined multitargeted approach in a randomized placebo-controlled trial, using celecoxib, L-carnitine, curcumin and lactoferrin, was able to improve the nutritional and immunometabolic alterations of cachexia, ameliorate the patient quality of life and correct cancer-related anemia. 96 Practical (individual reports) multimodal care programs for cancer cachexia have been recently published. 97 Another critical factor that may positively contribute to cancer cachexia treatment is a proper staging of the cachectic condition in cancer patients.…”
Section: A Multitarget Approach Including Physical Exercisementioning
confidence: 99%